2014
DOI: 10.1016/j.najef.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Banks’ capital, regulation and the financial crisis

Abstract: Banks' Capital, Regulation and the Financial Crisis This paper investigates whether regulatory capital requirements play an important role in determining banks' equity capital. We estimate equity capital regressions using panel data of a sample of 560 banks for 2004-2010. Our results suggest that regulatory capital requirements are not first order determinants of banks' capital structure. We document differences on the effect of most factors on banks' share of equity according to the type of bank and to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…Chen et al (2014) study the stock market integration between frontier and leading markets during the periods of pre-and post-global financial crisis. Črnigoj and Verbič (2014), Teixeira et al (2014), Yamamoto (2014) and Wan and Jin (2014) …”
Section: Monetary Policy Announcementsmentioning
confidence: 99%
“…Chen et al (2014) study the stock market integration between frontier and leading markets during the periods of pre-and post-global financial crisis. Črnigoj and Verbič (2014), Teixeira et al (2014), Yamamoto (2014) and Wan and Jin (2014) …”
Section: Monetary Policy Announcementsmentioning
confidence: 99%
“…These reductions had stronger effects on larger banks. More recently, Gropp and Heider () and Teixeira et al () provided evidence that banks that pay more often dividends tend to show more financial robustness and fewer problems in obtaining external financing.…”
Section: Related Literaturementioning
confidence: 99%
“…First, on the set of bank‐specific determinants, the effect of the dividend policy is still unexplored. A recent study by Ashraf and Zheng () recognizes that the dividend policy may even be more important for banks than for nonfinancial firms, as dividends may increase banks' external ratings (Bolding & Legget, ), may signal future growth opportunities (Abreu & Gulamhussen, ), or may reveal banks' financial robustness (Teixeira, Silva, Fernandes, & Alves, ). In this context, it is particularly important to understand how banks' dividend policy influences future profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Peura and Keppo (2005) call this excess capital "hedging" against breaches of minimum capital, and estimate some average percentage values for excess capital of between 2.4% and 3.5% above the regulatory minimum. Studies by Teixeira, Silva, Fernandes, andAlves (2014), andVanHoose (2007), showed that banks maintain excess capital in order to avoid emergency recapitalization costs. Flannery and Rangan (2008), in a study regarding big banks in the United States in the 90s, provided evidence of post-recession capital growth, with banks accumulating, on average, 75% of capital above the regulatory minimum, in a rational reply on the part of the banking market to the measure of withdrawing implicit government guarantees.…”
Section: Bibliographic Reviewmentioning
confidence: 99%